From Complaint to Satisfaction: The Role of Complaint Management System in Patient Satisfaction - Ni Wayan Pratita; Gede Sri Darma (CV. RADJA PUBLIKA, 2026)
This study aims to analyze the effect of the Complaint Management System (CMS) on patient satisfaction with trust as a mediating variable at Tangguwisia Regional Hospital and Giri Emas Regional Hospital, both Class D government hospitals in Buleleng Regency, Bali. The issue addressed in this study is the suboptimal implementation of the CMS, which has the potential to reduce patient trust and satisfaction with hospital services. This study examines: (1) the direct effect of CMS on patient satisfaction, (2) the effect of CMS on patient trust, (3) the effect of trust on patient satisfaction, and (4) the mediating role of trust in the relationship between CMS and patient satisfaction. The study used a quantitative approach with a cross-sectional survey design on 150 inpatients selected through a purposive sampling technique. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 application. The results showed that CMS had a positive and significant effect on both patient satisfaction and patient trust. Trust also had a significant effect on patient satisfaction and was proven to partially mediate the relationship between CMS and patient satisfaction. These findings demonstrate that a responsive, transparent, and solution-oriented complaint management system not only directly improves patient satisfaction but also strengthens patient trust, ultimately enhancing overall satisfaction. Academically, this study adds to the literature by confirming the role of trust as a crucial mediating variable in the context of Class D government hospitals in Indonesia.